2001
DOI: 10.1016/s0002-9440(10)62522-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Endothelin B Receptor at Protein and Gene Levels in Human Cirrhotic Liver

Abstract: Endothelin (ET) has been implicated in the regulation of hepatic microcirculation and development of portal hypertension. This study examined the localization of ETA receptor (ETAR) and ETB receptor (ETBR) in cirrhotic liver tissues from patients with hepatocellular carcinoma with hepatitis C-related cirrhosis, and normal liver samples from patients with metastatic liver carcinoma. Anti-ETAR and ETBR antibodies were used for immunohistochemistry and Western blot. Immunoelectron microscopy was conducted using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
5
32
0
Order By: Relevance
“…Less abundant mRNAs may need the use of multiple probes hybridising to the same mRNA. The use of catalysed signal enhancement of PNA probes in fungi, as was done in mammalian systems (Larsen et al, 2003;Yokomori et al, 2001) will be hampered by the presence of the cell wall, as is the case with DNA probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less abundant mRNAs may need the use of multiple probes hybridising to the same mRNA. The use of catalysed signal enhancement of PNA probes in fungi, as was done in mammalian systems (Larsen et al, 2003;Yokomori et al, 2001) will be hampered by the presence of the cell wall, as is the case with DNA probes.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide nucleic acid (PNA) probes have been used to detect rRNA in situ in bacteria and yeasts (PerryOÕKeefe et al, 2001;Rigby et al, 2002;Worden et al, 2000) and mRNA in mammalian cells (Larsen et al, 2003;Yokomori et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that ET-1(1-31) more strongly bind to ET B or ET B -like receptor (Kitamura et al, 2003). Moreover, ET B receptor dominantly expressed in sinusoidal cells in the human and rat liver (Anand et al, 2001;Yokomori et al, 2001). It was not possible to identify ET-1(1-31)-like IR on stellate cells.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with cirrhosis, expression of both receptors on hepatic stellate cells was reported to be up-regulated, but receptor (Yokomori et al, 2001a). Using immunohistochemistry, ET B expression was also reported to be up-regulated in human cirrhotic liver, with low ET A expression detected in both normal and diseased liver (Yokomori et al, 2001b). Endothelin may also be an important regulator of sinusoid vascular resistance mediated by vasoconstriction of stellate cells, the main effector of sinusoid calibre (Rockey and Weisiger, 1996).…”
Section: Introductionmentioning
confidence: 97%